Power Relations and Challenges in Mangrove Ecosystem Management: The Case of the Tanjung Panjang Nature Reserve - Ahmad Gading; Andrinof Chaniago (International Journal Labs, 2026)
Mangrove ecosystems play a crucial role in maintaining coastal ecological balance, protecting shorelines from abrasion, supporting biodiversity, and sustaining the livelihoods of coastal communities. However, the Tanjung Panjang Nature Reserve in Gorontalo Province has experienced severe mangrove degradation due to the expansion of shrimp pond activities and weak environmental governance. This study aims to analyze the power relations and challenges among actors involved in mangrove ecosystem management in the Tanjung Panjang Nature Reserve. The research employed a qualitative exploratory approach using political ecology and access theory frameworks. Data were collected through in-depth interviews, field observations, and literature studies involving government agencies, shrimp farmers, NGOs, and local communities. The findings reveal that mangrove management is strongly influenced by unequal power relations between stakeholders. Shrimp pond entrepreneurs possess stronger structural and relational access through capital, political networks, social identity, and market control, enabling them to maintain illegal pond operations despite conservation policies. Meanwhile, the Natural Resources Conservation Agency (BKSDA) faces significant limitations in budget, personnel, technology, and institutional coordination, reducing its effectiveness in restoration and law enforcement efforts. NGOs and local communities contribute to advocacy and conservation initiatives, yet their influence remains constrained by limited resources and weak policy implementation. The study concludes that successful mangrove restoration requires stronger institutional collaboration, consistent law enforcement, and inclusive governance that balances ecological sustainability with the socioeconomic needs of local communities.